Electronic J Biol 2019
DOI: 10.36648/1860-3122.15.3.79
|View full text |Cite
|
Sign up to set email alerts
|

A Screening Pilot Study on the Relation between Body Mass Index, and Heavy Metal and Mineral Levels in College Students

Abstract: Obesity is a chronic metabolic disease identified by excessive fat deposition in the body with the highest risk of disordered lipid profile. Obesity and inappropriate lifestyles such as smoking and fake food not only influence blood lipids but also helps heavy metals and mineral be absorbed and adhered to the tissues with minimal disposal, that producing health problems with ages. A total of 49 female students (18-35 years old) included in this study to assess the relationship between body mass index, heavy me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(26 citation statements)
references
References 29 publications
2
24
0
Order By: Relevance
“…Iron with vitamin B12 is also one of erythrocyte formation [9, 21, and 22]. As in the present results, there is a negative relationship between BMI and Iron and vitamin B 12 that it was females' effect than males, which may be due to diet, malabsorption due to the accumulation of body fat, a different change in hormones and genetic of different sex [1,2,8,9].…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Iron with vitamin B12 is also one of erythrocyte formation [9, 21, and 22]. As in the present results, there is a negative relationship between BMI and Iron and vitamin B 12 that it was females' effect than males, which may be due to diet, malabsorption due to the accumulation of body fat, a different change in hormones and genetic of different sex [1,2,8,9].…”
Section: Discussionsupporting
confidence: 58%
“…For instance, NHANES data was used to conclude that folate and B-complex vitamin deficiency can lead to congenital disabilities, anemia, leukemia, stress, and depression in adults [5][6][7]. A nutritional assessment can be done through anthropometry, biochemical methods, clinical methods, and dietary method [7][8][9]. The present study aims to measure biochemical profile and level of Vitamin B12, Fe, cortisol in the volunteer's population, and BMI in adult obese females and males subjects compared to the reference range.…”
Section: Introductionmentioning
confidence: 99%
“…Phenobarbital [ 27 , 28 , 29 ] and formaldehyde are present in our daily lives in chemicals, pharmacological treatments, and food additives; however, they are carcinogenic and can cause health issues, including inflammation, and neuropsychological disturbances, such as depression and stress [ 30 , 31 , 32 , 33 , 34 ]. Stress can be initiated in the body by chemicals and heavy metals [ 1 , 30 ], as well as physical, emotional, and psychiatric factors. Psychological stress occurs when individuals are under mental, physical, or emotional pressure that exceeds their ability to adapt to it or cope with it.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, we reported that K, Na, Ca, Fe, and Zn produced many beneficial health effects by decreasing C-reactive protein levels, as well as having anti-inflammatory and antioxidant effects. Additionally, these elements support both the immune and endocrine systems against opportunistic bacteria and fungi [ 1 , 51 , 53 ]. In both our past work and current studies, we found that pomegranate contains phytochemicals, including squalene, gamma-tocopherol, cis-11-eicosenamide, hexadecanamide, hydroxymethylfurfural, stigmastan-3,5-diene, oleamide, pentanoic acid, and octadecanoic acid, which have antiapoptotic, anti-inflammatory, antioxidant, antibacterial, and antifungal activities ( Table 2 ) [ 22 , 23 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation